Bio-based admixture applied to calcined clay-limestone low-carbon cement system as well as preparation method and application of bio-based admixture
By using bio-based admixtures in the calcined clay-limestone low-carbohydrate cement system, a spatial cross-network structure is formed, and the problem of rapid fluidity loss under high clay content is solved, the fluidity and dispersion of concrete are improved, and the system performance is enhanced.
Patent Information
- Application Number
- CN202311308313.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-11
- Publication Date
- 2025-04-11
AI Technical Summary
Calcined clay-limestone low-carbohydrate cement system loses fluidity quickly under high clay content, making it difficult to ensure the flow performance and dispersion of concrete, limiting its large-scale utilization in the concrete industry.
A bio-based admixture is used, which consists of a chain segment including segment A, segment B, segment C and segment D. It is connected to the cement-based material through polar groups, and the electrostatic attraction is acted upon and clay adsorbed, forming a spatial cross-network structure between the cement-based material and clay, reducing the influence of clay on the flow properties of concrete and improving the dispersion of clay.
It effectively reduces the impact of clay on admixtures, improves the flowability and dispersion of concrete, enhances the performance of the low-carbohydrate cement system of calcined clay-limestone, and promotes the loss of flowability of cement slurry during time.
Smart Images

Figure CN119798557A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of building materials, and more specifically, to a bio-based admixture for use in a calcined clay-limestone low-carbon cement system, and a preparation method and application thereof. Background Art
[0002] In recent years, global warming and ecological degradation caused by the increase of greenhouse gases have posed severe challenges to the traditional industrialization of mankind. Cement-based building materials, especially concrete or mortar, are widely used in various projects. Since the cement production process itself and the energy plants that generate electricity for the production process produce carbon dioxide, cement production is currently the main source of carbon dioxide atmospheric emissions. The "Technical Roadmap for Low-Carbon Transformation of the Cement Industry" jointly issued by relevant international organizations and the "White Paper on Low-Carbon Cement" issued by the United Nations Environment Program's Low-Carbon Cement Working Group both proposed technical approaches to achieve low-carbon development of cement concrete in the future: (1) reduce the output of silicate cement and improve the utilization efficiency of cement in concrete; (2) increase the proportion of alternative fuels and raw materials in cement production; (3) add auxiliary cementitious materials to reduce the amount of clinker; (4) develop new low-carbon cementitious materials; (5) increase the service life of concrete structures and reduce carbon emissions throughout the life cycle. Among them, the most effective and convenient method is to add mineral admixtures such as fly ash and mineral powder to cement clinker as auxiliary cementitious materials. At present, a large number of mineral admixtures have been used in the preparation of concrete, which can significantly improve the performance of concrete and reduce carbon emissions. However, with the rapid development of commercial concrete in my country, a large number of high-quality mineral admixtures have been basically consumed. The remaining industrial waste such as slag and fly ash are either not very active and difficult to ensure strength, or are expensive and have long transportation distances, making them difficult to use widely. Therefore, exploring new mineral admixtures with a wide range of sources and excellent performance and developing new low-carbon cementitious systems are the only way to achieve sustainable and low-carbon development in the cement concrete industry.
[0003] Calcined clay-limestone low carbon cement system, also known as LC 3 LC is a new type of low-carbon cementitious system that adds calcined clay and limestone to the original silicate cement system. Studies have shown that clay containing kaolinite has a higher pozzolanic activity after being calcined at 700℃-850℃. 3 The volcanic ash reaction of calcined clay and the interaction between limestone and calcined clay improve the cementitious properties of the material. Its typical ratio contains 50% Portland cement clinker, 30% calcined clay, 15% limestone powder and 5% gypsum. Since the calcination temperature of clay is lower than that of cement clinker and the calcination process does not emit carbon dioxide, compared with Portland cement, LC 3 Production can reduce CO2 emissions by up to 40%, and has broad application prospects.3 The working performance of system concrete is worse than that of ordinary Portland cement concrete. It requires higher water consumption or water reducing agent dosage at the same fluidity, which also limits its large-scale use in the concrete industry.
[0004] LC 3 The fluidity loss of the system is faster than that of silicate cement. This is mainly because the clay minerals in the calcined clay are layered structures. Their huge specific surface area will absorb a large amount of polycarboxylate water reducer, making it unable to continuously play a dispersing role. Although the surface of the calcined clay particles is negatively charged, in the cement paste, through Ca 2+ The complexation effect will also adsorb a large number of polycarboxylate water-reducing agent molecules.
[0005] Regarding improving the anti-clay performance of concrete admixtures, a common way is to introduce anti-clay functional monomers to change the structure of polycarboxylic acid water-reducing agent molecules to improve their anti-clay performance, thereby improving the fluidity of concrete. Alginate is extracted from brown algae and is composed of β-D-mannuronic acid (M segment) and α-L-guluronic acid (G segment) structures, which are connected by α-1,4 glycosidic bonds to form an irregular linear natural polysaccharide polymer. The molecular structure of alginate contains abundant carboxyl groups and hydroxyl groups, and it is easy to modify the chemical structure through oxidation, reductive amination, graft copolymerization, amidation and Ugi reactions. Relevant literature has pointed out that polymer structures with large steric hindrance have an inhibitory effect on the interlayer intercalation adsorption of polycarboxylic acid molecules on clay, and the irregular linear units of alginate just form a large steric hindrance, thereby hindering the adsorption of more polycarboxylic acid molecules on clay.
[0006] However, the above anti-clay methods mainly reduce the influence of clay on admixtures and concrete properties by reducing the interlayer adsorption of polycarboxylic acid molecules on clay. This is generally aimed at conventional concrete systems, but for LC with high clay content 3 System-wise, the effect is not obvious. Summary of the invention
[0007] The present application provides a bio-based admixture for use in a calcined clay-limestone low-carbon cement system, and a preparation method and application thereof. The bio-based admixture of the present application is applied to a calcined clay-limestone low-carbon cement system, which can not only effectively reduce the impact of clay on the admixture, but also help to improve the dispersibility of clay in the cement system, thereby improving the performance of concrete.
[0008] In the first aspect, the present application provides a bio-based admixture for use in a calcined clay-limestone low-carbon cement system, using the following technical solution: A bio-based admixture for use in a calcined clay-limestone low-carbon cement system, the bio-based admixture comprising segments including segment A, segment B, segment C and segment D; wherein the structure of segment A is shown in the following formula (I): (I) In formula (I), R1 is H or CH3, and n is an integer from 45 to 95; The structural formula of the segment B is shown in the following formula (II): (II) The structural formula of the segment C is shown in the following formula (III): (III) In formula (III), R2 is H or CH3; The structural formula of the segment D is shown in the following formula (IV): (IV) In formula (IV), M represents an alkali metal ion; The bio-based admixture is connected to the cement-based material through the polar groups in the chain segment, and is connected to the clay through the electrostatic attraction of the chain segment B. The polyether chain segment formed by the chain segment A and the linear structure formed by the chain segment D form a spatial cross-network structure between the cement-based material and the clay.
[0009] Furthermore, the bio-based admixture is prepared by free radical copolymerization of raw materials including monomer A, monomer B, monomer C and monomer D under the action of an initiator and a chain transfer agent, wherein monomer A is methyl allyl polyoxyethylene ether or allyl polyoxyethylene ether, monomer B is dimethyl diallyl ammonium chloride, monomer C is methacrylamide or acrylamide, and monomer D is alginate; the molar ratio of monomer A, monomer B, monomer C and monomer D is 1:6:(15-25):(0.05-0.15).
[0010] By adopting the above technical scheme, first of all, the bio-based admixture prepared by the present application has polar groups such as carboxyl groups distributed on the main chain and the side chain in the molecular structure, forming a dual adsorption site that acts on cement-based materials, which can effectively improve the adsorption capacity of the biological admixture on cement-based materials, and then fully realize the high water reduction function. At the same time, the dimethyl diallyl ammonium chloride in the present application is used as the source of segment B, and the cationic dimethyl diallyl ammonium chloride segment side chain with quaternary ammonium salt can be introduced into the bio-based admixture, that is, segment B, which can be adsorbed between the clay crystal layers by electrostatic attraction, so as to realize the connection between the bio-based admixture and the clay. At the same time, the use of methyl allyl polyoxyethylene ether or allyl polyoxyethylene ether can introduce a long side chain polyether segment, that is, segment A, and the polyether segment of the present application can form a spatial cross double network structure with the linear structure of the alginate segment, that is, with segment D, to form a sufficiently thick isolation layer between the cement-based material and the clay. Therefore, compared with the conventional introduction of functional groups to reduce the adsorption of clay and water reducer by steric hindrance, the present application converts "negative adsorption" into "beneficial adsorption", so that the bio-based admixture of the present application is adsorbed between cement-based materials and clay. Moreover, in the process of the bio-admixture being adsorbed between cement-based materials and clay, due to the linear structure of the polyether segment and the alginate segment forming a spatial cross-double network structure, in which the alginate segment has a larger conformation size in the aqueous solution, it hinders the intercalation adsorption of the long side chain polyether segment between the clay layers. Therefore, the admixture forms a fixed-point directional adsorption with the clay by virtue of the electrostatic attraction of segment B, and at the same time, a sufficiently thick and stable "isolation zone" is formed between the clay and the cement base, which can reduce the influence of clay on the flow properties of concrete on the one hand, and on the other hand, it is conducive to the uniform dispersion of clay in the concrete system and improves the performance of the calcined clay-limestone low-carbon cement system. In addition, for the admixture of the present application, as the hydration reaction proceeds, that is, the pH of the cement system rises, the glycosidic bonds on the molecular structure of the alginate segment will break and degrade, gradually unlocking the bonded water molecules, which has a promoting effect on improving the time-dependent fluidity loss of the cement slurry.
[0011] In summary, the admixture involved in the present application can also play a good role in the calcined clay-limestone low carbon cement system with high clay content, has good clay resistance, and can also improve the dispersibility of the calcined clay-limestone low carbon cement system, thereby improving its performance.
[0012] Furthermore, the weight average molecular weight of the alginate is 20-50 kDa, and the viscosity is less than 100 mPa.S. The weight average molecular weight of the monomer A is 2-5 kDa.
[0013] By adopting the above technical solution, alginate is higher than the molecular weight and viscosity range, and has low solubility, which is not conducive to modifying its structure.
[0014] Furthermore, the initiator is composed of a single oxidant, which includes one of persulfate, water-soluble azo compound and peroxide. The amount of the initiator is 0.1-0.7% of the total molar number of the monomer. The chain transfer agent is a thiol chain transfer agent, which includes at least one of mercaptopropionic acid, thioglycolic acid, mercaptoethanol, mercaptoethylamine and dodecanethiol, and the amount of the chain transfer agent is 2.5-5.0% of the total molar number of the monomer. The weight average molecular weight of the bio-based admixture is 80-120 kDa, and the PDI is 2-3.
[0015] In a second aspect, the present application provides a method for preparing a bio-based admixture for use in a calcined clay-limestone low-carbon cement system, using the following technical solution: A method for preparing a bio-based admixture for a calcined clay-limestone low-carbon cement system comprises the following steps: mixing monomers A, B, C and D, an initiator and a chain transfer agent, reacting for 4-8 hours at a temperature of 30-50° C., and obtaining the bio-based admixture through free radical copolymerization. The free radical copolymerization is a water system free radical copolymerization reaction, and the polymerization concentration of the free radical copolymerization reaction is 10-15%.
[0016] In a third aspect, the present application provides an application of a bio-based admixture applied to a calcined clay-limestone low carbon cement system in a calcined clay-limestone low carbon cement system.
[0017] In summary, this application has the following beneficial effects: 1. Since the bio-based admixture of the present application contains segments A, B, C and D, on the one hand, the admixture can be connected and adsorbed on the cement-based material through the action of the carboxyl group, and on the other hand, it is connected through the electrostatic force and clay adsorption. At the same time, the admixture of the present application forms a spatial cross-network structure between the cement-based material and the clay, thereby forming a sufficiently thick isolation layer; not only by "fixing" the clay, thereby reducing the impact on the admixture, but also with the "isolation layer", the clay also has good dispersibility in the cement system. Therefore, the admixture involved in the present application not only has good clay resistance in the calcined clay-limestone low-carbon cement system with a high clay content, but also can improve the dispersibility of the calcined clay-limestone low-carbon cement system.
[0018] 2. The segments A and D in the present application can not only form a spatial cross double network structure, but also form a sufficiently thick isolation layer between the cement-based material and the clay. In addition, in the process of the biological admixture being adsorbed between the cement-based material and the clay, in the spatial cross double network structure formed, the alginate segment has a larger conformation size in the aqueous solution, which hinders the intercalation adsorption of the long side chain polyether segment between the clay layers, so that the segment B can be more stably and smoothly adsorbed between the clay through electrostatic attraction.
[0019] 3. In the admixture of the present application, the alginate segment molecule, i.e., segment D, has abundant carboxyl and hydroxyl anion groups in its structure. As the hydration reaction proceeds, the Na+ on the alginate segment unit will exchange ions with the Ca2+ on the surface of the cement particles, making the alginate segment more easily adsorbed on the surface of the cement particles and forming a hydration film by hydrogen bonding with the free water in the pore fluid. As the hydration reaction proceeds, i.e., the pH of the cement system rises, the glycosidic bonds on the alginate segment molecular structure will break and degrade, gradually unlocking the bonded water molecules, which has a promoting effect on improving the time-dependent fluidity loss of the cement slurry. DETAILED DESCRIPTION
[0020] The present application is further described in detail below with reference to the embodiments.
[0021] Example The present application embodiment provides a bio-based admixture for use in a calcined clay-limestone low-carbon cement system, wherein the bio-based admixture is composed of segments including segment A, segment B, segment C, and segment D; wherein the structure of segment A is shown in the following formula (I): (I) In formula (I), R1 is H or CH3, and n is an integer from 45 to 95; The structural formula of segment B is shown in the following formula (II): (II) The structural formula of segment C is shown in the following formula (III): (III) In formula (III), R2 is H or CH3; The structural formula of segment D is shown in the following formula (IV): (IV) In the formula (IV), M represents an alkali metal ion.
[0022] The weight average molecular weight of the bio-based admixture is 80-120 kDa, and the PDI is 2-3.
[0023] In addition, the weight average molecular weight of the bio-based admixture for the calcined clay-limestone low-carbon cement system in the embodiment is determined by Shimadzu LC-20A high performance gel chromatograph (GPC), wherein the chromatographic column is TSKTSKG4000PWXL series, the column temperature is 25°C, the eluent is 0.1M sodium acetate aqueous solution, the flow rate is 0.5ml / min, the injection volume is 15μl 1‰ sample aqueous solution, and the standard curve is prepared using dextran standards (Sigma-Aldrich).
[0024] The present application also provides a method for preparing a bio-based admixture for use in a calcined clay-limestone low-carbon cement system, as follows: Raw materials: monomer A, monomer B, monomer C and monomer D, monomer A is methyl allyl polyoxyethylene ether or allyl polyoxyethylene ether, monomer B is dimethyl diallyl ammonium chloride, monomer C is methacrylamide or acrylamide, and monomer D is alginate; the molar ratio of monomer A, monomer B, monomer C and monomer D is 1:6:(15-25):(0.05-0.15).
[0025] Further, alginate is a commercial product with a weight average molecular weight of 20-50 kDa and a viscosity of less than 100 mPa.S. Methyl allyl polyoxyethylene ether or allyl polyoxyethylene ether is a commercial product with a weight average molecular weight of 2-5 kDa; dimethyl diallyl ammonium chloride is a commercial product; methacrylamide or acrylamide is a commercial product.
[0026] The initiator is composed of a single oxidant, which includes one of persulfate, water-soluble azo compound and peroxide. The amount of the initiator is 0.1-0.7% of the total molar number of the monomer. The chain transfer agent is a thiol chain transfer agent, which includes at least one of mercaptopropionic acid, thioglycolic acid, mercaptoethanol, mercaptoethylamine and dodecanethiol. The amount of the chain transfer agent is 2.5-5.0% of the total molar number of the monomer.
[0027] Preparation steps: Mix monomer A, monomer B, monomer C and monomer D, as well as an initiator and a chain transfer agent, react at a temperature of 30-50°C for 4-8 hours, and obtain a bio-based admixture through a free radical copolymerization reaction. The free radical copolymerization reaction is a free radical copolymer reaction in a water system, and the polymerization concentration of the free radical copolymerization reaction is 10-15% The following is an explanation through specific examples.
[0028] Example 1 Table 1 Raw material ratio table of the embodiment (feed ratio is the molar ratio of monomer A, monomer B, monomer C, and monomer D) Table 2 Process parameters of the embodiment (the amount of initiator and chain transfer agent is the percentage of the total molar number of monomers) Comparative Example The difference between Comparative Examples 1 and 2 and the embodiment is that the raw materials and preparation process conditions of the admixtures are different, as shown in Table 3 and Table 4 for details.
[0029] Table 3 Raw material ratio table of comparative example (feed ratio is the molar ratio of monomer A, monomer B, monomer C, and monomer D) Table 4 Process parameters of comparative examples (initiator and chain transfer agent dosage is percentage of total molar number of monomers) Application Examples The application example of the present application provides a calcined clay-limestone low carbon cement system (LC 3 ).
[0030] The calcined clay-limestone low carbon cement system is composed of a mixture of the following materials: (1) 30 parts by mass of calcined clay (CC) (2) 15 parts by mass of limestone (L) (3) 55 parts by mass of Portland cement (P) The composition, particle size and burning vector analysis tables of the calcined clay-limestone low-carbon cement system in the application example are shown in Tables 5 to 7. The composition was measured by the Thermo Fisher ADVANT XP X-ray fluorescence spectrometer, and the particle size composition was measured by the Anton Paar PSA1190LD laser particle size analyzer, wherein the calcined clay, limestone and Portland cement are all commercially available products.
[0031] Table 5 LC3 raw material composition Table 6 LC3 raw material particle size analysis table Table 7 LC3 raw material loss on ignition data The difference between Application Examples 1-12 is that the sources and dosages of bio-based admixtures are different, as shown in Table 8 for details.
[0032] Table 8 Sources and dosage of bio-based admixtures in application examples 1-12 Comparative Application Examples The difference between the comparative application example and the application example is that the source and dosage of the bio-based admixture are different, as shown in Table 9.
[0033] Performance testing: Refer to the test method in GB / T 8077-2012 "Test Method for Homogeneity of Concrete Admixtures". The admixtures in the application examples and comparative application examples were evaluated for their effects on the fluidity of the freshly mixed calcined clay-limestone low-carbon cement paste and its loss over time, with a fixed water-cement ratio of 0.30. In addition, a comparative group was set up, and the admixture in the comparative group was the commercially available Cologne KL-1030 anti-mud and collapse-preserving admixture, in which the admixture dosage in comparative group 1 was 12%, and the admixture dosage in comparative group 2 was 15%. The experimental results are shown in Table 10.
[0034] Table 10 Performance test results According to the performance comparison between application examples 1-8 and control group 1, under the same admixture dosage, the initial net slurry fluidity and 1h slurry fluidity of the newly mixed slurry of application examples 1-8 are higher than those of control group 1. Therefore, for the admixture of the present application, compared with the traditional cement dispersant, the bio-based admixture of the present application, even when applied to the calcined clay-limestone low-carbon cement system with a high clay content, has the characteristics of low dosage, high water reduction rate and excellent collapse retention performance. This is because the admixture in the present application is different from the technical solution in the prior art that introduces functional groups and reduces the contact between clay and admixtures. The present application actively connects the admixture to cement-based materials and clay at the same time. In the bio-based admixture of the present application, polar groups such as carboxyl groups in the admixture can be used to adsorb and connect with cement materials, so as to fully realize the high water reduction function. At the same time, the electrostatic attraction of segment B is used to adsorb between the clay crystal layers, so that the bio-based admixture and the segments A and D of the clay form a spatial cross double network structure, forming a sufficiently thick isolation layer between the cement-based material and the clay. This application converts "negative adsorption" into "beneficial adsorption", which can not only reduce the impact of clay on the flow properties of concrete, but also facilitate the uniform dispersion of clay in the concrete system and improve the performance of the calcined clay-limestone low-carbon cement system.
[0035] By comparing the technical solutions of application examples 1-4, it can be seen that the admixtures in application examples 1-4 have different source monomers for each segment when the raw material feed ratio is the same. It was finally found that the performance of application example 3 is better than that of other application examples. This is because the final molecular weight of the admixtures in application examples 1-4 is different, and a larger or smaller molecular weight is not conducive to the admixture to exert its working performance. This is because the carboxylic acid groups in the main chain and side chain structure of the admixture have a strong affinity for the cementitious material, so the admixture can be fixed on the surface of the cement particles, and segment A and segment D form a spatial cross double network structure. When the admixture has a high molecular weight, the molecular conformation is too large, and the main chain structure will cause a cage effect on the carboxylic acid group. When the molecular weight is too low, the low content of the carboxylic acid group will cause the admixture to be unable to be fixed on the surface of the cement particles, affecting the performance of the admixture.
[0036] Further comparison of the performance of Application Example 5 and Application Example 6 shows that the performance of Application Example 5 is better than that of Application Example 6, which indicates that when the number of repeating units of segment C is small, there will be too few adsorption groups in the admixture and the dispersion performance will be too low. Comparison of the performance of Application Example 7 and Application Example 8 shows that the performance of Application Example 7 is better than that of Application Example 8, which indicates that the number of repeating units of segment D, i.e., the alginate segment, should not be too high. If it is too high, the admixture itself will be entangled and agglomerated, and it will not be able to disperse the LC. 3 The system forms an effective dispersion.
[0037] Analysis of the performance of Application Examples 9 to 12 shows that when the amount of bio-based admixture increases, LC 3 The initial fluidity of the fresh cement paste and its time-dependent fluidity will increase slowly, but if the dosage continues to increase, the above-mentioned working performance of the system will show a significant downward trend, which proves that when the amount of bio-based admixture is too much, it may enter an adsorption supersaturation state. At this time, the dual adsorption sites of the main chain and side chain of the admixture will cause a bridge effect and prone to secondary agglomeration, which may cause the chain segments in the bio-based admixture to entangle with each other, reducing the initial dispersion performance of the system and ultimately leading to a decrease in the working performance of the system.
[0038] Compared with application examples 1 to 8, the working performance of comparative application example 1 is significantly lower than that of LC obtained by using the admixture of this application. 3 The working performance of the system proves that the lack of corresponding polyether segments means that the spatial cross-double network structure cannot be realized, and the "isolation zone" cannot be formed between the clay and cement-based materials, which will make it difficult to improve the initial fluidity of the system; it is further found that the working performance of comparative example 2 is also poor, proving that relying solely on polyether segments is not enough to improve the initial fluidity of LC 3 In order for the system to be effectively dispersed, the alginate segments, namely segment D and segment A, need to cooperate to form a spatial cross-double network structure, thereby improving the dispersibility of the admixture.
[0039] Further analysis of the performance of comparative application example 3 shows that the amount of dimethyldiallyl ammonium chloride in the admixture of comparative application example 3 is reduced, and the performance of comparative application example 3 is reduced compared with the application example, indicating that there needs to be enough segments B in the admixture of the present application so that the admixture can be adsorbed between the clay crystal layers through electrostatic attraction. However, further analysis of the technical solution of comparative application example 4 shows that the amount of dimethyldiallyl ammonium chloride in comparative application example 4 is increased, which should allow the admixture to have more segments B, and then better adsorb with clay, thereby improving the performance of the cement system; however, in fact, the performance of comparative application example 4 has also decreased compared with the application example, which shows that there is a coordination relationship between the segments A, B and C and D of the present application, and too much of a segment will affect the overall structural performance of the admixture. Combining the performance of comparative application examples 5 and 6, it is found that no matter whether the polyether segment, i.e., segment A, is too much or too little, the final biological admixture has a poor effect on the performance of concrete, indicating that too much or too little segment A will affect its interaction with segment D, and thus affect the performance of the biological admixture.
[0040] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A bio-based admixture for use in a calcined clay-limestone low-carbon cement system, characterized in that: The bio-based admixture is composed of segments including segment A, segment B, segment C and segment D; wherein the structure of segment A is shown in the following formula (I): (Ⅰ) In formula (I), R1 is H or CH3, and n is an integer from 45 to 95; The structural formula of the segment B is shown in the following formula (II): (Ⅱ) The structural formula of the segment C is shown in the following formula (III): (Ⅲ) In formula (III), R2 is H or CH3; The structural formula of the segment D is shown in the following formula (IV): (Ⅳ) In formula (IV), M represents an alkali metal ion; The bio-based admixture is connected to the cement-based material through the polar groups in the chain segment, and is connected to the clay through the electrostatic attraction of the chain segment B. The polyether chain segment formed by the chain segment A and the linear structure formed by the chain segment D form a spatial cross-network structure between the cement-based material and the clay.
2. The bio-based admixture for use in a calcined clay-limestone low-carbon cement system according to claim 1, characterized in that: The bio-based admixture is prepared by free radical copolymerization of raw materials including monomer A, monomer B, monomer C and monomer D under the action of an initiator and a chain transfer agent, wherein the monomer A is methyl allyl polyoxyethylene ether or allyl polyoxyethylene ether, the monomer B is dimethyl diallyl ammonium chloride, the monomer C is methacrylamide or acrylamide, and the monomer D is alginate.
3. The bio-based admixture for use in a calcined clay-limestone low-carbon cement system according to claim 2, characterized in that: The molar ratio of the monomer A, the monomer B, the monomer C and the monomer D is 1:6:(15-25):(0.05-0.15).
4. The bio-based admixture for use in a calcined clay-limestone low-carbon cement system according to claim 2, characterized in that: The weight average molecular weight of the alginate is 20-50 kDa, and the viscosity is less than 100 mPa.S.
5. The bio-based admixture for use in a calcined clay-limestone low-carbon cement system according to claim 2, characterized in that: The weight average molecular weight of the monomer A is 2-5 kDa.
6. The bio-based admixture for use in a calcined clay-limestone low carbon cement system according to claim 2, characterized in that: The initiator is composed of a single oxidant, which includes one of persulfate, water-soluble azo compound and peroxide. The amount of the initiator is 0.1-0.7% of the total molar number of the monomers.
7. The bio-based admixture for use in a calcined clay-limestone low carbon cement system according to claim 2, characterized in that: The chain transfer agent is a mercaptan chain transfer agent, which includes at least one of mercaptopropionic acid, thioglycolic acid, mercaptoethanol, mercaptoethylamine and dodecanethiol. The amount of the chain transfer agent is 2.5-5.0% of the total molar number of the monomers.
8. The bio-based admixture for use in a calcined clay-limestone low carbon cement system according to claim 1, characterized in that: The weight average molecular weight of the bio-based admixture is 80-120 kDa, and the PDI is 2-3.
9. A method for preparing a bio-based admixture for use in a calcined clay-limestone low-carbon cement system as claimed in any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing monomer A, monomer B, monomer C and monomer D as well as an initiator and a chain transfer agent, reacting for 4-8 hours at a temperature of 30-50° C., and obtaining a bio-based admixture through free radical copolymerization.
10. Use of the bio-based admixture for calcined clay-limestone low carbon cement system according to any one of claims 1 to 8 in a calcined clay-limestone low carbon cement system.
Citation Information
Cited By
Low-carbon cement performance improver as well as preparation method and application thereof
CN121990781A